Towards net zero energy in industrial and commercial buildings in Portugal. (March 2020) - Bandeiras, F.; Gomes, M.; Coelho, P.; Fernandes, J.
Abstract: The contents of this paper address the concept of net zero energy in industrial and commercial buildings, focusing on the definition which accounts for energy losses by converting each energy carrier used in the building to source energy. Therefore, this paper presents a sample of several source energy conversion factors commonly used in the United States, Canada and in most European countries. Energy efficiency in industrial and commercial buildings is discussed throughout the work, including a brief review of energy-efficiency measures which can be implemented in order to increase the efficiency and improve the performance of these energy-intensive buildings. Net metering is introduced due to its importance towards achieving net zero energy, along with its potential benefits and challenges, as well as a brief overview of policies currently being implemented around the world. In addition, various aspects regarding the classification of the weighting system and calculation of zero energy balance are also addressed. Finally, a case study is presented to evaluate whether five distinct enterprises located in Portugal can achieve annual net zero energy by deploying on-site renewable sources in the area available within their site boundary. This case study is based on a developed algorithm which allows the evaluation of these enterprises according to different symmetric and asymmetric weighting systems. The concepts of demand response and net metering are also briefly discussed and presented as a viable and cost-effective solution to aid any building achieving annual net zero energy. Highlights: Energy efficiency is mandatory to achieve net zero energy in industrial buildings. Several process specific measures can be adopted in each industrial sector. Source energy conversion factors are presented to assist the balance calculation. The choice of weighting factors heavily influences the building energy balance. Asymmetric weights favouring generation are suitable for net zero-energy buildings.